2003
DOI: 10.1074/jbc.m300364200
|View full text |Cite
|
Sign up to set email alerts
|

Heme Oxygenase Inhibits Human Airway Smooth Muscle Proliferation via a Bilirubin-dependent Modulation of ERK1/2 Phosphorylation

Abstract: The aim of this study was to investigate whether the heme oxygenase (HO) pathway could modulate proliferation of airway smooth muscle (ASM) and the mechanism(s) involved in this phenomenon. In cultured human ASM cells, 10% fetal calf serum or 50 ng/ml platelet-derived growth factor AB induced cell proliferation, extracellular and intracellular reactive oxygen species (ROS) production and ERK1/2 phosphorylation. Pharmacological HO-1 induction (by 10 microm hemin or by 20 microm cobalt-protoporphyrin) and HO inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
62
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 51 publications
3
62
1
Order By: Relevance
“…Such a scenario could explain, at least in part, the lower level of apoptosis in bilirubin-treated hVSMC. Taillé et al (23) suggested that bilirubin in airway smooth muscle cells could also modulate the phosphorylation of ERK by a redox mechanism. Furthermore, bilirubin could also modulate other cell signaling pathways that are cross-talking with the ERK/ MAPK pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Such a scenario could explain, at least in part, the lower level of apoptosis in bilirubin-treated hVSMC. Taillé et al (23) suggested that bilirubin in airway smooth muscle cells could also modulate the phosphorylation of ERK by a redox mechanism. Furthermore, bilirubin could also modulate other cell signaling pathways that are cross-talking with the ERK/ MAPK pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, over-expression of HO-1 by either transfection of the HO-1 gene or exogenous administration of a certain HO-1 inducer reduces excessive VSMC proliferation [25] . However, the effect of HO-1 on cell proliferation is highly variable and seems to be cell-type specific [8,[26][27][28] , raising an important question of whether the antiproliferative effect of neferine on VSMC could be mediated via HO-1 expression. To test this, the effects on both HO-1 expression and growth inhibition of neferine were determined with the same concentration of neferine used in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidants, including ROS, are signals involved in the regulation of cell proliferation [40] . Results from Taille et al emphasize the concept that the antioxidant properties of the HO-bilirubin pathway are related not only to its ROS scavenging properties but also to the modulation of ROS production [27] . According to the above studies, although we have shown that HO-1 up-regulation by neferine participated in the inhibition of HUVSMC proliferation via suppression of ERK1/2 activation, we did not exclude the possibility that neferine may also induce the expression of other antiproliferative enzymes or that the effect of neferine may be achieved through the tightly regulated process of the multiple pathways that may be activated or inactivated by neferine.…”
Section: Discussionmentioning
confidence: 99%
“…Iron can induce iron-binding as well as iron-exporting proteins, HO-1, p21, and genes that are relevant to cell growth. Bile pigments are potent antioxidants by scavenging oxidants and decreasing the activity of NADPH oxidase (12,36); bile pigments also could inhibit extracellular signal-regulated kinase activation (49). Through such combined effects, products of HO-1 may contribute to the cytoprotective effects of HO-1.…”
Section: Ho-1 As a Protectant Against Heme/heme Protein-induced Renalmentioning
confidence: 99%